INVESTIGATING THE CADETS’ VOCABULARY LEARNING STRATEGIES AND THEIR MARITIME VOCABULARY MASTERY IN DIFFERENT ACADEMIC MAJORS - Sumarta, Ryan Puby; Hafita, Yuniar Ayu; Budiarte, Agus; Utami, Helidatasa (Universitas Muhammadiyah Makassar, 2024)
Vocabulary acquisition is crucial for language learners, impacting their overall linguistic proficiency and communication abilities. This research investigated the influence of vocabulary learning strategies and study programs on maritime cadets' vocabulary test results at Sorong Merchant Polytechnic. This study employed a quantitative methodology and an ex-post facto design. The sample consisted of 91 third-semester cadets from Sorong Merchant Marine Polytechnic, representing three study programs: Port and Shipping Management, Ship Engineering, and Nautical Studies. Data were collected through a questionnaire to assess vocabulary learning strategies and a vocabulary examination based on maritime-related queries. Statistical analyses revealed no significant differences in vocabulary test scores across academic programs and learning strategies, despite the popularity of the determination strategy. However, a two-way ANOVA indicated a significant interaction effect between vocabulary learning strategies and study programs (F(7, 77) = 2.477, p = .024). This suggests that specific combinations of learning strategies and study programs may enhance vocabulary test results more effectively than individual variables alone. Therefore, developing tailored teaching methods is crucial to improve learning outcomes. Further research should explore additional factors such as motivation, prior language proficiency, and learning environment support to optimize language learning outcomes.